Giant Swallowtail, Orangedog, Papilio cresphontes Cramer (Insecta: Lepidoptera: Papilionidae) - Heather J. McAuslane (EDIS)
Revised! EENY-008, a 5-page illustrated fact sheet by H. J. McAuslane, is part of the Featured Creatures collection. It describes this striking, wonderfully “exotic”-looking butterfly that is very abundant in Florida, and whose larva is the well-known “orangedog” that is a minor pest of sweet orange and other members of the citrus family — its distribution, description, life cycle, host plants, biological control and other control methods. Includes references. Published by the UF Department of Entomology and Nematology, September 2009.